The Impact of Mismatch Repair Status in Colorectal Cancer on the Decision to Treat With Adjuvant Chemotherapy: An Australian Population-Based Multicenter Study. (23rd March 2016) - He, Emily Y.; Hawkins, Nicholas J.; Mak, Gabriel; Roncolato, Felicia; Goldstein, David; Liauw, Winston; Clingan, Philip; Chin, Melvin; Ward, Robyn L.
Abstract: Background: Testing for mismatch repair (MMR) status in colorectal cancer (CRC) may provide useful prognostic and predictive information. We evaluated the impact of such testing on real-world practice regarding adjuvant chemotherapy for patients with resected CRC. Patients and Methods: A total of 175 patients with stage II and III mismatch repair-deficient (MMRD) CRC were identified from an Australian population-based study of incident CRCs. Their treatment decisions were compared with those for a cohort of 773 stage-matched patients with mismatch repair-proficient (MMRP) CRCs. The effect of MMR status, age, and pathologic characteristics on treatment decisions was determined using multiple regression analysis. Results: Overall, 32% of patients in stage II and 71% of patients in stage III received adjuvant chemotherapy. Among the stage II patients, those with MMRD cancer were less likely to receive chemotherapy than were MMRP cases (15% vs. 38%; p < .0001). In this group, the treatment decision was influenced by age, tumor location, and T stage. MMR status influenced the treatment decision such that its impact diminished with increasing patient age. Among patients with stage III tumors, no difference was found in the chemotherapy rates between the MMRD and MMRP cases. In this group, age was the only significant predictor of the treatment decision. Conclusion: The findings of this study suggest that knowledge of the MMR status of sporadic CRC influences treatment decisions for stage II patients, in an era when clear recommendations as to how these findings should influence practice are lacking. Abstract : Testing for mismatch repair (MMR) status in colorectal cancer (CRC) may provide useful prognostic and predictive information. The impact of such testing on real-world practices regarding adjuvant chemotherapy for resected CRC was evaluated. This study found that knowledge of MMR status influences treatment decisions for patients with stage II CRC, in an era when clear recommendations as to how these findings should influence practice were lacking.